2020
DOI: 10.3991/ijim.v14i14.15047
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Research Competence of Students by Means of Mobile Education

Abstract: The article outlines the need of reforming the higher education system, which should be aimed at educating graduates who are able to coordinate their future professional activities independently by means of mobile education. The authors conclude that this is impossible without the formation of research competence of students during their studies at the university. One of the main tasks of higher education is not only to present information to students, but to form the ability to obtain it independently, to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…The results found show that research competences are both achieved and in progress. This result is consistent with the findings of Galustyan, Borozdin, Pleshakov, Askhadullina & Radchenko (2020) who analysed groups of graduate students and found that there was still a significant percentage of them who did not have autonomous research competences, which means that they are still in progress. Another important result is that students have no methodological design that is related to cognitive competence.…”
Section: Discussionsupporting
confidence: 91%
“…The results found show that research competences are both achieved and in progress. This result is consistent with the findings of Galustyan, Borozdin, Pleshakov, Askhadullina & Radchenko (2020) who analysed groups of graduate students and found that there was still a significant percentage of them who did not have autonomous research competences, which means that they are still in progress. Another important result is that students have no methodological design that is related to cognitive competence.…”
Section: Discussionsupporting
confidence: 91%